PENGAJARAN DAN PRAKTIK UJI POTENSI PREBIOTIK PANGAN FUNGSIONAL LOKAL DI SMA NEGERI 7 YOGYAKARTA - Ariestanti, Catarina; Nugroho, Wahyu Setyo; Kristiawan, Yoga Angkawijaya; Purba, Laurentia Henrieta Permita Sari; Restiani, Ratih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
Application of Biotechnology in Indonesia has been found in many sectors especially in food sector. One of the benefits is that it can be used to increase the nutritional value of food product so that it can be beneficial for health and decrease the risk of disease. The introduction of Biotechnology in utilizing local food product will increase students’ sensitivity about natural materials and their utilization. The purpose of this program was to introduce the role of Biotechnology in utilizing and processing agriculture by-product into beneficial edible end-product. This activity was divided into three stages: preparation, implementation, and reporting the activity. Preparation was done by contacting 7 State Senior High School as a partner. Implementation was conducted in partner’s Laboratory of Biology by delivering the teaching materials, continued with producing banana corm cookies and checked its prebiotik capability. Banana corm cookies were successfully produced. In vitro study showed that Lactobacillus plantarum FNCC-0265 were able to grow in banana corm cookies substituted media. The students showed a positive response during the activity, and it was shown by creation of the cookies and their ability to use drop plate technique for bacterial enumeration in vitro.